2012
DOI: 10.1039/c1ee02684d
|View full text |Cite
|
Sign up to set email alerts
|

One-pot catalytic hydrocracking of raw woody biomass into chemicals over supported carbide catalysts: simultaneous conversion of cellulose, hemicellulose and lignin

Abstract: Using raw lignocellulosic biomass as feedstock for sustainable production of chemicals is of great significance. Herein, we report the direct catalytic conversion of raw woody biomass into two groups of chemicals over a carbon supported Ni-W 2 C catalyst. The carbohydrate fraction in the woody biomass, i.e., cellulose and hemicellulose, were converted to ethylene glycol and other diols with a total yield of up to 75.6% (based on the amount of cellulose & hemicellulose), while the lignin component was converted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
327
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 384 publications
(353 citation statements)
references
References 34 publications
9
327
2
4
Order By: Relevance
“…They were able to convert these molecules to C 9 -C 18 cycloalkanes using Pd/C, 5% H 3 PO 4 and 4 MPa H 2 in water at 523 K. Although the studies mentioned above have successfully converted lignin, these studies did not simultaneously upgrade all three biomass fractions. A recent study has addressed this simultaneous conversion by treating ashtree in the presence of a Ni-W 2 C/AC catalyst in water at 508 K. 171 A 76% yield of diols (mostly ethylene glycol) was obtained from the hemicellulose and cellulose portions of biomass along with a 36% yield of lignin monomers (mostly syringyl propanol and propyl syringol). Various studies have investigated the conversion of isolated forms of lignin, notably, those forms obtained as a side product of pulp and paper processes such as Kraft lignin, sulfite lignin or organosolv lignin.…”
Section: Lignin Monomersmentioning
confidence: 99%
“…They were able to convert these molecules to C 9 -C 18 cycloalkanes using Pd/C, 5% H 3 PO 4 and 4 MPa H 2 in water at 523 K. Although the studies mentioned above have successfully converted lignin, these studies did not simultaneously upgrade all three biomass fractions. A recent study has addressed this simultaneous conversion by treating ashtree in the presence of a Ni-W 2 C/AC catalyst in water at 508 K. 171 A 76% yield of diols (mostly ethylene glycol) was obtained from the hemicellulose and cellulose portions of biomass along with a 36% yield of lignin monomers (mostly syringyl propanol and propyl syringol). Various studies have investigated the conversion of isolated forms of lignin, notably, those forms obtained as a side product of pulp and paper processes such as Kraft lignin, sulfite lignin or organosolv lignin.…”
Section: Lignin Monomersmentioning
confidence: 99%
“…Recently, yields of up to 50% of propyl-substituted guaiacol and syringol have been reported via a nickel-catalyzed fragmentation-hydrolysis 5 or the nickel/tungsten carbidecatalyzed hydrocracking of birch wood. 6 Other reported reductive processes generally resulted in lower yields and more complex product mixtures consisting of multiple aromatic products, 7,8 or even ring-hydrogenated monomeric products. 9 Such one-step, reductive processes generally lead to the formation of bis-or tris-oxygenated mono-aromatic molecules, however.…”
Section: Introductionmentioning
confidence: 99%
“…30 Zhang et al have shown that woody lignin is catalytically hydrogenated to guaiacol and syringols at 235 C under 6 MPa H 2 , and has obtained 46% (based on lignin) phenolic compounds. 31 Other catalysts, such as CuCr oxide, 32 Co-Mo-S/Al 2 O 3 , 33 activated carbon-, alumina-or silica-supported Ru [34][35][36][37] or Pt, 38,39 have also been reported in hydrogenation of lignin or model compounds to monomeric phenols. Nickel-based catalysts have shown excellent chemoselectivity for aromatic products or high activity for C-O bond cleavage, as reported by Hartwig 40 and Rinaldi.…”
Section: Introductionmentioning
confidence: 99%